Answer:
Explanation:
We are given the following information in the question:
y intercept = 4, -8
The circle passes through the point (-12, -8)
Equation of circle:
![(x-h)^2 + (y-k)^2 = r^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4eirzo410e5djazi04h0efdsewkok5jdnt.png)
where r is the radius of circle, (h,k) is the center of circle.
The circle passes through the points (0,4), (0,-8_ and (-12,-8)
Putting these points in the equation of circle we get:
![1) (0-h)^2 + (4-k)^2 = r^2\\h^2 + (4-k)^2 = r^2\\2) (0-h)^2 + (-8-k)^2 = r^2\\h^2 + (-8-k)^2 = r^2\\3) (-12-h)^2 + (-8-k)^2 = r^2\\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ia4mupzymkr0ie39jf22aey3ru0a4pqq2i.png)
Now, we have three equations in three variables.
Solving the three equations, we obtain:
h = -6, k = -2, r =
![6\sqrt2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7cly6nm281txw2s8xyy97idnhy6ezcer0q.png)
Putting these values in the equation of circle:
![(x-(-6))^2 + (y-(-2)) = (6√(2))^2\\(x+6)^2 + (y+2)^2 = 72](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g8zjn2drndxxfld10lgsb618pqti45z2bl.png)
The above equation is the required equation of circle.